Women and stroke: disparities in clinical presentation, severity, and short- and long-term outcomes - Naveed, Hiba; Almasri, Muna; Kazani, Bahram; Nauman, Areej; Akhtar, Naveed; Singh, Rajvir; Kamran, Saadat; Al Jerdi, Salman; Thermalingem, Sathvika; Shuaib, Ashfaq (Frontiers in Neurology, 2023)
Objectives: There is limited data on sex-related short-term and long-term stroke outcomes from the Middle East. We present eight years of experience from the Qatar stroke database. Setting: The Qatar stroke database prospectively collects data on all stroke patients admitted to Hamad General Hospital. For this study we compared the admission characteristics and short-term (modified Rankin Scale {mRS}) and major adverse cardiovascular events {MACE)long-term outcomes in male versus female patients. Participants: 7300 patients (F: 1406 {19.3%} and M: 5894 {80.7%}, mean age 55.1±13.3 {F 61.6±15.1, M 53.5±12.3; p<0.001}) were admitted with acute ischemic stroke. Primary and secondary outcome measures: Significantly fewer females presented within the 4.5 hours of onset [F: 29% versus M: 32.8%; p = 0.01]. Although women had more severe stroke [NIHSS >10; F: 19.9 % versus M: 14.5 %; P <0.001], fewer were treated with thrombolysis [F: 9.8% versus M: 12.1%; p 0.02]. Women had more medical complications [F: 11.7% versus M: 7.4%; p<0.001] and a prolonged length of stay in hospital [F: 6.4±7.6 versus M: 5.5±6.8; p<0.001]. Results: Good outcome at 90-days less frequent in women [mRS of 0-2: F: 53.3% versus M: 71.2%; p<0.001]. Fewer female patients were on antiplatelets [F: 78% versus M: 84.8%; p<0.001] or statins [F: 81.2% versus M: 85.7%; p<0.001]. Significantly more females had MACE [F: 12.6% versus M: 6.5%; p<0.001]. Conclusions: Older age at presentation contributes to the poor outcome following an acute stroke in females. Other contributing factors include delays in admission to hospital, lower rates of thrombolysis and fewer preventative treatments.